2009
DOI: 10.1002/cphc.200900078
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Preferences of the Full Chicken Prion Protein in Solution and Its Differences with Respect to Mammals

Abstract: We investigate the conformations of the full chicken prion protein (ChPrP1-267) in solution at neutral pH with molecular dynamics simulations. We focus on the persistence of its secondary structure motifs using a recently proposed protein chirality indicator [A. Pietropaolo et al., Proteins 2008, 70, 667-677]. From this, we find a high rigidity of helix 2 (ChPrP178-195) and of the hexarepeat domain, which is turn rich, and a plasticity of the short beta-sheet, consistent with the available NMR structural detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…Interestingly, the structural role played by water molecules was analyzed by a molecular dynamics approach [91], highlighting that the bound and buried water that stabilizes a β-bulge between one edge of the sheet and helix 3, could prevent the avian PrP C aggregation. This finding was also supported by a 130 ns long molecular dynamics simulation of the full avian prion protein chPrP1-267, which finds again the latter bulge and a water molecule tightly bound to the Valine 168 [92]. Moreover, a rigid domain in the hexarepeat region was found, revealing a hydrogen bond mainly between the imidazole nitrogen of histidine 72 and the phenolic hydrogen of tyrosine 64, found also in the tetra-hexarepeat fragment [84].…”
Section: The Avian Prion and Its Difference From Mammal Analoguesupporting
confidence: 61%
“…Interestingly, the structural role played by water molecules was analyzed by a molecular dynamics approach [91], highlighting that the bound and buried water that stabilizes a β-bulge between one edge of the sheet and helix 3, could prevent the avian PrP C aggregation. This finding was also supported by a 130 ns long molecular dynamics simulation of the full avian prion protein chPrP1-267, which finds again the latter bulge and a water molecule tightly bound to the Valine 168 [92]. Moreover, a rigid domain in the hexarepeat region was found, revealing a hydrogen bond mainly between the imidazole nitrogen of histidine 72 and the phenolic hydrogen of tyrosine 64, found also in the tetra-hexarepeat fragment [84].…”
Section: The Avian Prion and Its Difference From Mammal Analoguesupporting
confidence: 61%
“…Those involve the shortening of the β sheet involving L82–L120 and the transition from the α helix to the type I β turn involving residues P5–R9 (Figure S2). However, the structural transition from an α helix to a type I β turn occurs easily in proteins under standard conditions. , In line with the other states, the closed “D” state also deviates from the “A” state in the tertiary structure [C α RMSD from the X-ray structure of 10 Å (Figure S1a)]. A shortening of the TrkA β sheet is observed in the L82–L120 section, as well as the stabilization of a 3 10 helix involving residues I6–H8 of NGF chains (Figure S2).…”
Section: Resultsmentioning
confidence: 66%
“…7,8 The globular fold of the mammalian PrP c is also maintained in the avian counterpart 9,10 and both N-terminal domains are featured by tandem amino-acid repeats (PHNPGY in avians, PHGGGWGQ in mammals). [11][12][13] Notably, prion diseases are only observed in mammals, appearing to be precluded from occurring in avian species. 14 The physiological function of PrP c is unknown, even if it is widely recognized that the prion protein binds copper in vivo, and this interaction is required for its biological role.…”
Section: Introductionmentioning
confidence: 99%
“…Prion diseases are associated with the accumulation of a misfolded pathogenic form (PrP sc ) of the endogenous prion protein (PrP c ), a membrane-bound glycoprotein normally expressed in the central nervous system (CNS) of all mammals. Nuclear magnetic resonance (NMR) studies performed on recombinant human PrP c proteins demonstrated that the C-terminal region, starting approximately at residue 125, adopts a globular fold that is largely helical, along with a small two-stranded β-sheet. Conversely, the N-terminal region, containing approximately 120 residues, is unstructured and flexible in solution. There are currently no high-resolution structures for PrP sc , but it is known that the β-sheet content is increased during pathogenic conversion. , The globular fold of the mammalian PrP c is also maintained in the avian counterpart , and both N-terminal domains are featured by tandem amino-acid repeats (PHNPGY in avians, PHGGGWGQ in mammals). Notably, prion diseases are only observed in mammals, appearing to be precluded from occurring in avian species …”
Section: Introductionmentioning
confidence: 99%